Mothers' Experiences of Genetic Counselling in Johannesburg, South Africa. Issue 1 (15th August 2014) - Morris, Megan; Glass, Merlyn; Wessels, Tina‐Marié; Kromberg, Jennifer G. R.
Abstract: Genetic counselling is offered in diverse settings, and patient reactions vary due to differences in personal, family and community beliefs, local healthcare settings, as well as cultural background. Together, these factors influence how individuals experience genetic counselling. This study aimed to describe and document the experiences of thirteen mothers, with children with Down syndrome, oculocutaneous albinism or haemophilia B, who had received genetic counselling at state hospitals in Johannesburg, South Africa. A qualitative research design drawing on principles of Interpretative Phenomenological Analysis was used. Four voice‐recorded focus groups were conducted and the resulting data were analysed using thematic content analysis. Five themes were identified in the data: thrown into the unknown; a worthwhile experience; a break in communication; telling the family and the community; and spreading the word. It was seen that genetic counselling cannot be viewed as a singular experience, but rather as one which is influenced by mothers' lived experiences and their interactions with other healthcare services, family and community members. The results from this study showed that genetic services and conditions were poorly understood, that the experience of genetic counselling varied amongst mothers, and on‐going patient support is needed particularly when addressing family and community members. Further research is needed to assess what information is valuable to individuals during genetic counselling and how to deliver this information in a contextually appropriate manner. Greater awareness of genetic conditions is also required amongst communities and healthcare professionals. Valuable insight was gained from this study which can be used to improve local training programmes and genetic counselling services in Johannesburg, and in South Africa.